Effects of increasing CO2 on trees and intensively monitored plots: research needs in view of future ecosystem studies - Michopoulos, P (IForest (Viterbo), 2011)
The intensively monitored plots in Europe have offered a lot of information with regard to the dynamics of forest ecosystems. A large stock of data is already available as an input to ecological models. The carbon sequestration challenge is a little different from others. It requires long-term studies and additional information from what already exists. So far, apart from the determination of organic C in soils, research in the intensively monitored plots has mainly focused on above ground processes, i.e., crown assessment, phenology, deposition, litterfall, tree growth, and foliar chemistry. All these parameters are valuable and will continue to be so. However, according to the latest literature reviews on the subject, the key to understanding the reaction of trees to climate change lies in the dynamics of belowground processes. Information is needed on nitrogen mineralization rates, soil respiration rates and labile carbon forms in soils. If we take into account that countries pay for their carbon emissions and are paid for carbon sequestration, a research like this can be worth doing. Most importantly, the ecological models can be enriched and therefore be more precise in predicting tree response to climate change.